Investigating the Effects of Intrinsic Motivation and Emotional Appeals Into the Link Between Organic Appeals Advertisement and Purchase Intention Toward Organic Milk - Wang, Jianming; Dang, Wilson; Hui, Wang; Muqiang, Zheng; Qi, Wu (Frontiers in Psychology, 2021)
Consumers care about healthy food. Thus, several firms use organic appeals advertising to change consumer attitudes and persuade them to purchase organic food. Organic appeals advertisement often presents content that provides information and knowledge about organic elements of a food product (e.g., health, safety, non-chemicals, and rich nutrition). In contrast, non-organic appeals advertisement does not present information about organic elements of a food product. This study aims to clarify the effect of organic appeals advertisement on consumer motivations and behavior. It uses stimuli-organism-response model and self-determination motivation theory to investigate the relationship between organic appeals advertisement and purchase intention toward organic milk considering the mediating role of intrinsic motivation and the moderating role of emotional appeals. Two experimental designs are used to test the hypotheses. Results show that consumers receiving organic appeals advertisement have a higher intention to purchase organic milk than those receiving non-organic appeals advertisement. Furthermore, intrinsic motivation is found to have a mediating role in the link between organic appeals advertisement and purchase intention. In other words, when consumers receive advertisements of an organic milk product, they have higher intrinsic motivation and hold higher intention to purchase organic milk products. Furthermore, emotional appeals have a moderating effect on the relationship between organic appeals advertisement and intrinsic motivation. The influence of organic appeals advertisement on intrinsic motivation is stronger when emotional appeals are positive and weaker when emotional appeals are negative.